Development of participative methodologies for genetic improvement of bean in Honduras. - Rosas, Juan Carlos (Agronomía Mesoamericana, 2006)
Even though it is recognized that traditional plant breeding approaches have been effective on increasing yields and solving pest problems that limit crop production, it is still argued that the levels of adoption, and expected impacts, have been limited. Small farmers who produced most of the basic grains are included under this context; they do not posses the resources to change their environment to obtain the yield responses that are expected from improved varieties with higher potential. However, in the case of beans in Central America, improved varieties developed by conventional plant breeding methods have been valuable in reducing the dissemination of diseases that could have caused severe yield reductions in the region, i.e. bean golden yellow mosaic. Participatory plant breeding (PPB), which involves an active farmer participation in the development of varieties for specific adaptation, is an alternative for increasing the access and adoption of improved varieties by small farmers who have limited access to improved technologies and/or use low inputs. In Central America, already exists some initiatives of PPB in bean and maize crops; regarding with these initiatives, the interests and expectations of farmers, organizations and donors have increased recently. This publication intents to provide some guidelines on the application of PPB approaches for the genetic improvement of the common bean; it is based in the experience obtained by breeders of the Bean Research Program of Zamorano, during the first two years of a project conducted in collaboration with technical personnel of a nongovernmental organization and farmers from various communities of Yorito and the Lago Yojoa in Honduras.